Temperature and strain self-compensated refractometer based on turning point of Mach–Zehnder interference in three-core fiber - Wei, Yefen (2023)
We demonstrate an in-line Mach–Zehnder interference with a dispersion turning point (DTP) by sandwiching a section of three-core fiber (TCF) between two short no-core fibers (NCFs). The interference occurs mainly between the center core mode and a cladding mode of the TCF, which are excited and recoupled by the two NCFs. Two interference dips flanking the DTP are sensitive to ambient refractive index (RI) but shift oppositely. Moreover, the interval between these two dips responds linearly to ambient RI as well and has a higher sensitivity (−67.56 nm/RIU) within the RI range from 1.3518 to 1.4003. Meanwhile, the third dip near the DTP shows relatively low sensitivity to RI but is highly sensitive to temperature. By using the different responses of the third dip and the interval between flanking dips, this device is proposed to apply as a RI sensor with the compensation scheme of temperature. Finally, all three interference dips show very low sensitivity to axial strain, and the disturbance of strain can be further depressed by using the interval as the indicator.